Creep-plasticity-fatigue calculations in the design of porous double layers for new transpiration cooling systems. (October 2021) - Skamniotis, Christos; Cocks, Alan C.F.
Highlights: Porous double layer cooling systems experience severe nominal thermal stresses. These stresses can increase 4 times at film holes causing local reverse plasticity. Plasticity dominates over creep in the cyclic strain range that leads to fatigue. Neuber type schemes and cyclic inelastic FE analysis predict similar strain range. A low cool wall thickness and a low film hole inclination improve fatigue life. Abstract: New porous double layer (PDL) transpiration cooling technologies can allow gas turbine entry temperatures to be increased beyond current limits towards higher engine efficiency. However, PDL systems require inclined film holes with stress concentration factors in excess of 3.8. Combination of thermoelastic Finite Element (FE) analysis with Neuber type local strain approaches gives similar cyclic strain range predictions with cyclic plasticity-creep FE analysis. Fatigue crack initiation at film holes occurs with a low number of cycles due to excessive plasticity. Our study establishes links between elastic-inelastic analyses and between material phenomena-PDL geometry and indicates pathways of improving life.